A COMMUNITY SERVICE EDUCATION ABOUT CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) FOR SCHOOL-AGE CHILDREN AT SDN 1 BULIAN - Ayu Rusmeni, Ni Putu Diah; Rismayanti, I Dewa Ayu; Ayuni Tania, Ni Luh Linda; Merthasari, Ni Ketut Putri; Sundayana, I Made (STIKes William Booth Surabaya, 2025)
Clean and healthy living behavior or known as PHBS is one form of action in achieving a degree of health that can be applied as early as possible. Actions to maintain cleanliness to achieve optimal health must be trained to be carried out starting from oneself so that it can become a good habit in the future both for one's own health and the environment. The purpose of this community service activity is to provide knowledge and understanding of PHBS to elementary school children. The activity was carried out at SD Negeri 1 Bulian which is located in Kubutambahan Village, Buleleng Regency. Educational activities were carried out in the form of counseling with the lecture method. Educational materials were displayed in the form of powerpoints and examples were given directly with an interesting delivery that was easy for school children to understand. The implementation of PHBS education went well, and the students were enthusiastic and actively asked questions during the discussion process. All participated in the activity until it was finished.